Carbon fiber reinforced thermoset resin based composite braided rope and method of reinforcing with same
Patent Information
- Application Number
- CN202611129824.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,现有技术在处理致密三维混编复合绳时面临浸渍深度与施工适用期难以兼顾的问题
[0023]1、本发明通过采用氯化胆碱-咪唑低共熔溶剂对双酚A型环氧树脂进行粘度调节与咪唑活性锁定,在常温下获得低粘度且适用期长的潜伏性浸渍树脂体系,有效解决了大型构件现场缠绕施工中树脂适用期不足的技术瓶颈。
Smart Images

Figure CN122980200A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials and building structure reinforcement technology, specifically to a carbon fiber reinforced thermosetting resin-based composite braided rope and a method for reinforcing its components. Background Technology
[0002] Carbon fiber reinforced thermosetting resin matrix composites are widely used in the reinforcement of building structural beams and columns, long-span bridge beams, and special industrial components due to their lightweight and high strength properties. To further improve the shear strength, abrasion resistance, and high-temperature stability of reinforcing ropes, silicon carbide fibers are typically introduced into the carbon fiber matrix for three-dimensional weaving. These high-density hybrid weaves require deep impregnation with thermosetting resin, followed by winding or anchoring onto the surface of the component to be reinforced and completing cross-linking and curing to form a complete load-bearing system.
[0003] However, existing technologies face the challenge of balancing impregnation depth and application period when processing dense three-dimensional braided composite ropes. Thermosetting resins have inherently high viscosity, making it difficult for them to naturally penetrate the core of high-density braided structures, resulting in unimpregnated areas within the material. Adding conventional volatile solvents to the resin to reduce viscosity leads to solvent evaporation during subsequent heating and curing, leaving numerous micropores within the composite rope, resulting in a loose structure and weakened mechanical properties. Conversely, using a low-viscosity, two-component, fast-curing resin system causes the cross-linking reaction to begin immediately after mixing, leading to a rapid increase in system viscosity and an extremely short application period, failing to meet the tensioning and winding time requirements for large components in on-site construction.
[0004] Furthermore, in existing technologies, polyacrylonitrile-based carbon fiber bundles are typically coated with epoxy sizing agents to improve bundle cohesion. However, the presence of these sizing agents hinders subsequent chemical bonding between the resin matrix and the fiber surface, resulting in insufficient interfacial shear strength. Conventional acetone extraction or high-temperature desizing processes are energy-intensive and time-consuming, and it is difficult to introduce active functional groups onto the fiber surface. The interfacial bonding force of heterogeneous fibers and the driving mechanism for deep impregnation are also unresolved technical bottlenecks in existing technologies. Silicon carbide fibers have strong chemical inertness and low interfacial shear strength with conventional epoxy resin matrices. Existing chemical grafting or plasma surface pretreatment processes are cumbersome and difficult to apply directly to continuous long-scale three-dimensional braided ropes. At the same time, conventional external physical methods such as pressure impregnation suffer from severe fluid penetration attenuation when dealing with three-dimensional braided fabrics with high fiber volume content, failing to achieve complete filling of the core voids of the fiber network by the resin. These factors collectively lead to the defects of existing reinforced composite ropes having high internal porosity and easy shear delamination at the interlayer interface after curing. Summary of the Invention
[0005] To address the problems mentioned in the background art, the first aspect of the present invention provides a carbon fiber reinforced thermosetting resin-based composite braided rope.
[0006] The composite braided rope is composed of a surface-modified fiber-reinforced substrate and a latent impregnation resin system; the fiber-reinforced substrate includes carbon fiber bundles and silicon carbide fiber bundles, wherein the total fiber volume content of the composite braided rope is 55% to 65%, and in the total fiber volume, the carbon fiber bundles account for 70% to 80%, and the silicon carbide fiber bundles account for 20% to 30%; and the carbon fiber bundles and / or the silicon carbide fiber bundles are surface-cleaned and activated by a eutectic solvent before being mixed and woven to remove the sizing agent on the fiber surface and introduce hydroxyl active sites on the fiber surface.
[0007] Preferably, the carbon fiber bundle is a polyacrylonitrile-based continuous carbon fiber bundle with a surface carbon content greater than or equal to 94%; the silicon carbide fiber bundle is a continuous silicon carbide fiber bundle with an oxygen mass fraction on the fiber surface less than or equal to 1.5%; the bisphenol A type epoxy resin has an epoxy equivalent of 184 g / eq to 194 g / eq at 25°C and a dynamic viscosity of 10000 mPa·s to 15000 mPa·s at 25°C.
[0008] Preferably, the total fiber volume content of the composite braided rope is 60%, the carbon fiber bundle accounts for 75% of the total fiber volume, and the silicon carbide fiber bundle accounts for 25% of the total fiber volume; each 100 parts by weight of the bisphenol A type epoxy resin contains 20 parts by weight of the eutectic solvent, and the molar ratio of choline chloride to imidazole in the eutectic solvent is [missing information]. .
[0009] Preferably, the fiber-reinforced substrate adopts a three-dimensional multi-directional braided structure, with the carbon fiber bundle serving as the axial load-bearing core yarn and the silicon carbide fiber bundle interwoven around the core yarn as a wear-resistant and interface transition braided yarn; the ends of the composite braided rope lead out a portion of the internal continuous carbon fiber bundle to serve as conductive connection terminals for external power supply. After the latent impregnation resin system is fully cured, the terminal hydroxyl groups in the choline chloride form a hydrogen bond network with the silanol groups on the surface of the silicon carbide fiber bundle.
[0010] A second aspect of the present invention provides a method for preparing and reinforcing the carbon fiber reinforced thermosetting resin-based composite braided rope described in the first aspect, comprising the following steps:
[0011] Preparation steps of eutectic solvent: Choline chloride and imidazole are heated and mixed to obtain a homogeneous eutectic solvent;
[0012] Fiber surface pretreatment steps: Immerse carbon fiber bundles and / or silicon carbide fiber bundles in the eutectic solvent, and treat them at a constant temperature of 75°C to 85°C for 30 to 60 minutes under inert gas protection. After removal, rinse with anhydrous ethanol and dry to obtain surface-modified fiber bundles.
[0013] Hybridization molding step: The surface-modified carbon fiber bundles and silicon carbide fiber bundles are three-dimensionally hybridized to obtain a dry hybridized rope;
[0014] Latent resin preparation steps: At room temperature, the eutectic solvent is mixed with bisphenol A type epoxy resin and degassed to obtain a latent impregnation resin system;
[0015] Electric field driven impregnation step: The dry hybrid rope is immersed in the latent impregnation resin system. An external alternating pulse electric field is applied to induce electroosmotic flow in the resin system inside the hybrid rope. After impregnation, the rope is taken out, and the resin mass fraction is controlled to be 30% to 40%.
[0016] Component surface anchoring step: Wrap the impregnated hybrid rope around the surface of the component to be reinforced and apply pre-tightening force to fix it;
[0017] Thermally activated in-situ curing step: External heating is applied to the reinforced area to increase the temperature in stages, dissociating the hydrogen bonds in the eutectic solvent to release imidazole, and in-situ crosslinking and curing the bisphenol A type epoxy resin.
[0018] Preferably, in the eutectic solvent preparation step, the specific preparation method of the eutectic solvent is as follows: under the protection of an inert gas, choline chloride and imidazole powder are weighed according to a predetermined molar ratio and placed in a reaction vessel equipped with a reflux condenser; the heating temperature is controlled at 75°C to 85°C, mechanical stirring is turned on, and the mixture is stirred at a constant temperature for 2 to 4 hours until the solid mixture is transformed into a homogeneous and transparent liquid, and then cooled to 25°C for later use.
[0019] Preferably, the specific process parameters for the electric field driven impregnation step are as follows: connect the parallel anode plate in the impregnation tank to the high-potential output terminal of the pulse power supply, and connect the continuous carbon fiber bundle lead-out end of the dry hybrid rope to the low-potential output terminal of the pulse power supply; apply an alternating pulse electric field, setting the electric field strength to 10V / cm to 25V / cm, the pulse frequency to 5kHz to 20kHz, the duty cycle to 40% to 60%, and maintain the pulse electric field for 10 to 30 minutes.
[0020] Preferably, during the application of the alternating pulsed electric field, the temperature of the resin system is controlled between 25°C and 35°C by a closed-loop temperature control system and an external circulating water cooling jacket, and the highest local temperature does not exceed 40°C.
[0021] Preferably, the stepped temperature rise parameters of the thermally activated in-situ curing step are as follows: first, the temperature is increased to 110°C to 120°C at a rise rate of 1°C / min to 2°C / min, and held at a constant temperature for 1.5 to 2 hours for pre-curing; then, the temperature is increased to 140°C to 160°C at a rise rate of 1°C / min to 2°C / min, and held at a constant temperature for 2 to 3 hours for post-curing; and finally, the temperature is allowed to cool naturally after curing.
[0022] The present invention, by adopting the above technical solution, can bring the following beneficial effects:
[0023] 1. This invention uses a choline chloride-imidazolium eutectic solvent to adjust the viscosity of bisphenol A epoxy resin and lock the imidazolium activity, thereby obtaining a low-viscosity, long-potential latent impregnation resin system at room temperature, which effectively solves the technical bottleneck of insufficient resin potential in on-site winding construction of large components.
[0024] 2. This invention significantly improves the resin's ability to penetrate and fill the core of the high-density three-dimensional braided structure by applying an alternating pulsed electric field during the impregnation process and initiating electroosmotic flow through the periodic oscillation migration of free ions in the eutectic solvent. At the same time, it avoids the generation of gas by electrolytic side reactions under a DC electric field, thereby greatly reducing the macroscopic porosity of the composite braided rope.
[0025] 3. In the thermally activated curing stage, the present invention causes the eutectic solvent to dissociate and release imidazole, thereby achieving in-situ crosslinking of epoxy resin and forming a hydrogen bond network between the terminal hydroxyl groups of choline chloride and the silanol groups on the surface of silicon carbide fiber. This significantly improves the efficiency of interfacial shear stress transfer between the resin matrix and the heterogeneous fiber, and enhances the interlaminar shear strength and axial tensile properties of the composite braided rope.
[0026] 4. This invention applies choline chloride-imidazolium eutectic solvent simultaneously to the surface modification treatment of carbon fiber bundles and the latent curing of epoxy resin, realizing the integration of solvent for fiber surface cleaning and activation and resin system compatibilization, simplifying the process flow, and significantly improving the chemical anchoring density of the fiber-resin interface. Attached Figure Description
[0027] Figure 1 A flowchart illustrating the process steps of the component reinforcement method for carbon fiber reinforced thermosetting resin-based composite braided rope provided in an embodiment of the present invention;
[0028] Figure 2 This is a schematic diagram illustrating the principle of the latent and in-situ dissociation mechanism of the eutectic solvent provided in this embodiment of the invention;
[0029] Figure 3 This is a comparison diagram of the porosity distribution of composite braided ropes in the embodiments and comparative examples of the present invention;
[0030] Figure 4This is a comparison diagram of the axial tensile mechanical properties of the composite braided rope in the embodiments and comparative examples of the present invention. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Please see the appendix Figure 1-4 This invention provides a carbon fiber reinforced thermosetting resin-based composite braided rope and a method for reinforcing its components.
[0033] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0034] Carbon fiber, CAS number 7440-44-0, is a continuous polyacrylonitrile-based carbon fiber bundle with a tensile strength grade of T700. Each bundle has a 12K fiber specification, a surface carbon content greater than or equal to 94%, and a bulk density of [missing information]. ;
[0035] Silicon carbide fiber, CAS number 409-21-2, is a continuous silicon carbide fiber bundle with a linear density of 500 tex and a single fiber diameter of [missing information]. The oxygen mass fraction on the fiber surface is less than or equal to 1.5%, and the bulk density is... ;
[0036] Bisphenol A type epoxy resin, commercial model E-51, CAS number 1675-54-3, epoxy equivalent at 25℃ is... to The dynamic viscosity at 25℃ is to Its molecular structure is characterized by a high molecular weight compound containing a bisphenol A backbone and terminal epoxy groups, with an average relative molecular mass of 380.
[0037] Choline chloride, CAS number 67-48-1, chemical name 2-hydroxyethyltrimethylammonium chloride, molecular formula is It appears as a white crystalline powder with a purity greater than or equal to 98% and a melting point of [missing information]. ;
[0038] Imidazole, CAS number 288-32-4, chemical name 1,3-diazazole, molecular formula is It appears as white crystals with a purity greater than or equal to 99% and a melting point of [missing information]. to .
[0039] Preparation Example
[0040] Preparation Example 1:
[0041] This preparation example provides a method for preparing a eutectic solvent, comprising the following steps:
[0042] In an inert gas glove box, according to the molar ratio of choline chloride to imidazole: Accurately weigh choline chloride and imidazole;
[0043] Place the weighed mixture of choline chloride and imidazole powder into a three-necked flask equipped with a mechanical stirrer and a reflux condenser.
[0044] Place the three-necked flask in a heated oil bath and control the heating temperature to [temperature value missing]. ;
[0045] Turn on the mechanical stirrer, set the speed to 300 rpm, and stir at a constant temperature for 3 hours until the solid mixture completely destroys the original crystal lattice structure and transforms into a uniform and transparent liquid.
[0046] Stop heating and cool the reaction product to... Store in a sealed, light-protected container to obtain the eutectic solvent.
[0047] Preparation Example 2:
[0048] This preparation example provides a method for preparing a eutectic solvent, comprising the following steps:
[0049] In an inert gas glove box, according to the molar ratio of choline chloride to imidazole: Accurately weigh choline chloride and imidazole;
[0050] Place the weighed mixture of choline chloride and imidazole powder into a three-necked flask equipped with a mechanical stirrer and a reflux condenser.
[0051] Place the three-necked flask in a heated oil bath and control the heating temperature to [temperature value missing]. ;
[0052] Turn on the mechanical stirrer, set the speed to 200 rpm, and stir at a constant temperature for 4 hours until the solid mixture completely destroys the original crystal lattice structure and transforms into a uniform and transparent liquid.
[0053] Stop heating and cool the reaction product to... Store in a sealed, light-protected container to obtain the eutectic solvent.
[0054] Preparation Example 3:
[0055] This preparation example provides a method for preparing a eutectic solvent, comprising the following steps:
[0056] In an inert gas glove box, according to the molar ratio of choline chloride to imidazole: Accurately weigh choline chloride and imidazole;
[0057] Place the weighed mixture of choline chloride and imidazole powder into a three-necked flask equipped with a mechanical stirrer and a reflux condenser.
[0058] Place the three-necked flask in a heated oil bath and control the heating temperature to [temperature value missing]. ;
[0059] Turn on the mechanical stirrer, set the speed to 400 rpm, and stir at a constant temperature for 2 hours until the solid mixture completely destroys the original crystal lattice structure and transforms into a uniform and transparent liquid.
[0060] Stop heating and cool the reaction product to... Store in a sealed, light-protected container to obtain the eutectic solvent.
[0061] Example
[0062] Example 1:
[0063] This embodiment provides a method for reinforcing carbon fiber reinforced thermosetting resin-based composite braided rope and its components, including the following steps:
[0064] A homogeneous eutectic solvent was prepared according to the method provided in Preparation Example 1; carbon fiber bundles were immersed in the eutectic solvent obtained in Preparation Example 1 and treated at 80°C for 45 minutes under nitrogen protection to remove the sizing agent on the surface and activate the fiber surface; the treated carbon fiber bundles were ultrasonically rinsed three times with anhydrous ethanol and vacuum dried at 60°C for 2 hours to obtain surface-modified carbon fiber bundles.
[0065] The surface-modified carbon fiber bundles are used as the axial load-bearing core yarn, and the silicon carbide fiber bundles are used as the wear-resistant and interface transition weaving yarn. They are mixed and woven using a three-dimensional multi-directional weaving machine with a weaving angle of 30 degrees. The total fiber volume content of the mixed rope is controlled to be 60%, of which carbon fiber accounts for 75% of the total fiber volume and silicon carbide fiber accounts for 25% of the total fiber volume. Continuous carbon fiber bundles are led out from the end of the mixed rope as conductive connection ends.
[0066] exist Under the conditions, the eutectic solvent was added dropwise to the epoxy resin at a uniform rate according to the ratio of 100 parts by mass of bisphenol A type epoxy resin and 20 parts by mass of the eutectic solvent obtained in Preparation Example 1. The mixture was stirred at 1000 rpm for 20 minutes using a high-speed disperser. The mixture was then placed in a vacuum degassing chamber and degassed for 25 minutes under an absolute pressure not exceeding 0.01 MPa to obtain a latent impregnation resin system.
[0067] The obtained latent impregnating resin system was injected into an insulating impregnation tank equipped with parallel anode plates. The anode plates were connected to the high-potential output terminal of a pulse power supply, and the continuous carbon fiber bundle lead-out end of the hybrid rope was connected to the low-potential output terminal of the pulse power supply. The dry hybrid rope was completely immersed in the impregnating resin system. The pulse power supply was turned on to apply an alternating pulse electric field, and the electric field strength was set to [value missing]. The pulse frequency is The duty cycle is 50%, and the resin system temperature is maintained at [temperature value] by an external circulating water cooling jacket. After maintaining the pulsed electric field for 20 minutes, the power is disconnected, the hybrid rope is led out of the impregnation tank and the excess resin on the surface is scraped off by a double roller extrusion device, and the resin mass fraction of the composite rope is controlled to be 35%.
[0068] The impregnated braided rope is wrapped around the surface of the component to be reinforced and applied. The initial preload is controlled by an external heating device for stepped temperature increase and curing, starting with... The heating rate was increased to And maintain the temperature at a constant level for 1.5 hours, then... The heating rate was increased to Maintain the temperature at this time for 2.5 hours, and after curing, use... Cooling rate to The reinforcement process was completed by removing the force-applying equipment.
[0069] Example 2:
[0070] This embodiment provides a method for reinforcing carbon fiber reinforced thermosetting resin-based composite braided rope and its components, including the following steps:
[0071] A homogeneous eutectic solvent was prepared according to the method provided in Preparation Example 2; carbon fiber bundles were used as axial load-bearing core yarns, and silicon carbide fiber bundles were used as wear-resistant and interface transition braiding yarns. The yarns were mixed and braided using a three-dimensional multi-directional braiding machine, with the braiding angle set at 20 degrees. The total fiber volume content of the mixed rope was controlled to be 55%, of which carbon fiber accounted for 70% of the total fiber volume and silicon carbide fiber accounted for 30% of the total fiber volume. Continuous carbon fiber bundles were led out from the end of the mixed rope as conductive connection ends.
[0072] exist Under the conditions, according to the ratio of 100 parts by mass of bisphenol A type epoxy resin and 18 parts by mass of the eutectic solvent obtained in Preparation Example 2, the eutectic solvent was added dropwise to the epoxy resin at a uniform rate, and the mixture was stirred at 800 rpm for 30 minutes using a high-speed disperser. The mixture was then placed in a vacuum degassing chamber and degassed for 25 minutes under an absolute pressure not exceeding 0.01 MPa to obtain a latent impregnation resin system.
[0073] The obtained latent impregnating resin system was injected into an insulating impregnation tank equipped with parallel anode plates. The anode plates were connected to the high-potential output terminal of a pulse power supply, and the continuous carbon fiber bundle lead-out end of the hybrid rope was connected to the low-potential output terminal of the pulse power supply. The dry hybrid rope was completely immersed in the impregnating resin system. The pulse power supply was turned on to apply an alternating pulse electric field, and the electric field strength was set to [value missing]. The pulse frequency is The duty cycle is 40%, and the resin system temperature is maintained at [temperature value missing] through an external circulating water cooling jacket. After maintaining the pulsed electric field for 30 minutes, the power is disconnected, the hybrid rope is led out of the impregnation tank and the excess resin on the surface is scraped off by a double roller extrusion device, and the resin mass fraction of the composite rope is controlled to be 30%.
[0074] The impregnated braided rope is wrapped around the surface of the component to be reinforced and applied. The initial preload is controlled by an external heating device for stepped temperature increase and curing, starting with... The heating rate was increased to And maintain the temperature for 2 hours, then... The heating rate was increased to Maintain the temperature for 3 hours, and after curing, use... Cooling rate to The reinforcement process was completed by removing the force-applying equipment.
[0075] Example 3:
[0076] This embodiment provides a method for reinforcing carbon fiber reinforced thermosetting resin-based composite braided rope and its components, including the following steps:
[0077] A homogeneous eutectic solvent was prepared according to the method provided in Preparation Example 3; carbon fiber bundles were used as axial load-bearing core yarns, and silicon carbide fiber bundles were used as wear-resistant and interface transition braiding yarns. The yarns were mixed and braided using a three-dimensional multi-directional braiding machine, with the braiding angle set at 45 degrees. The total fiber volume content of the mixed rope was controlled to be 65%, of which carbon fiber accounted for 80% of the total fiber volume and silicon carbide fiber accounted for 20% of the total fiber volume. Continuous carbon fiber bundles were led out from the end of the mixed rope as conductive connection ends.
[0078] exist Under the conditions, according to the ratio of 100 parts by mass of bisphenol A type epoxy resin and 24 parts by mass of the eutectic solvent obtained in Preparation Example 3, the eutectic solvent was added dropwise to the epoxy resin at a uniform rate, and the mixture was stirred at 1200 rpm for 15 minutes using a high-speed disperser. The mixture was then placed in a vacuum degassing chamber and degassed for 25 minutes under an absolute pressure not exceeding 0.01 MPa to obtain a latent impregnation resin system.
[0079] The obtained latent impregnating resin system was injected into an insulating impregnation tank equipped with parallel anode plates. The anode plates were connected to the high-potential output terminal of a pulse power supply, and the continuous carbon fiber bundle lead-out end of the hybrid rope was connected to the low-potential output terminal of the pulse power supply. The dry hybrid rope was completely immersed in the impregnating resin system. The pulse power supply was turned on to apply an alternating pulse electric field, and the electric field strength was set to [value missing]. The pulse frequency is The duty cycle is 60%, and the resin system temperature is maintained at [temperature value missing] through an external circulating water cooling jacket. After maintaining the pulsed electric field for 10 minutes, the power is disconnected. The hybrid rope is then led out of the impregnation tank and scraped off excess resin from the surface using a double-roller extrusion device, controlling the resin mass fraction of the composite rope to be 40%.
[0080] The impregnated braided rope is wrapped around the surface of the component to be reinforced and applied. The initial preload is controlled by an external heating device for stepped temperature increase and curing, starting with... The heating rate was increased to And maintain the temperature at a constant level for 1.5 hours, then... The heating rate was increased to Maintain the temperature at this time for 2 hours, and after curing, use... Cooling rate to The reinforcement process was completed by removing the force-applying equipment.
[0081] Comparative Example
[0082] Comparative Example 1:
[0083] Compared with Example 1, the difference is that in the impregnation process, no alternating pulsed electric field is applied, and impregnation is completed solely by the natural capillary physical immersion of the braided rope in the impregnation resin system, and the impregnation time is extended to 60 minutes, while the rest are the same.
[0084] Comparative Example 2:
[0085] Compared with Example 1, the difference is that in the impregnation process step, "turn on the pulse power supply to apply an alternating pulse electric field, and set the pulse frequency to..." Replace "duty cycle is 50%" with "apply the same electric field strength ( "a constant DC electric field", all others are the same.
[0086] Comparative Example 3:
[0087] Compared with Example 1, the difference is that in the latent impregnation resin system preparation step, the eutectic solvent obtained in Preparation Example 1 was not used, but was replaced by an equal mass of conventional reactive diluent (butyl glycidyl ether) and imidazole mixture. The actual mass of imidazole added was the same as in Example 1, and choline chloride was not added. In the fiber surface pretreatment step, an equal mass of conventional reactive diluent (butyl glycidyl ether) was used to replace the eutectic solvent to perform surface cleaning treatment on the carbon fiber bundles under the same conditions. The remaining process steps and parameters were the same.
[0088] Comparative Example 4:
[0089] Compared with Example 1, the difference is that silicon carbide fiber bundles were not introduced in the hybrid rope preparation step. Instead, pure carbon fiber bundles were used for three-dimensional multi-directional weaving, and the overall fiber volume content was controlled to be 60%. All other aspects were the same.
[0090] Test Case Description and Experimental Methods
[0091] Test Example 1: Macroscopic Physical Properties and Porosity Test of Composite Braided Rope
[0092] This test aims to verify the degree of densification of composite braided ropes under different impregnation processes and resin systems.
[0093] Experimental Procedure: The porosity of the composite material was tested according to ASTM D2734 standard. Completely cured composite braided rope samples from Examples 1 to 3 and Comparative Examples 1 to 4 were cut, with a length of [missing information]. The actual density of each sample was determined by hydrostatic weighing, using anhydrous ethanol as the test medium and at a constant test temperature. Meanwhile, the mass fraction of the matrix was tested by nitric acid digestion method, and the theoretical density of the composite material was calculated by combining the theoretical density of carbon fiber, silicon carbide fiber and cured resin matrix. Finally, the macroscopic porosity of the sample was calculated by the ratio of the difference between the actual density and the theoretical density. Five samples were measured in parallel for each set of process parameters and the average value was taken.
[0094] Experimental data:
[0095] Table 1. Test data of physical density and porosity of composite braided ropes in the examples and comparative examples.
[0096]
[0097] Test Example 2: Interfacial Mechanical and Axial Tensile Properties Test of Composite Braided Rope
[0098] This test aims to verify the influence of different component systems and processes on the final load-bearing capacity and interlayer bonding strength of the material.
[0099] Experimental Procedure: Short beam shear tests were conducted according to ASTM D2344 to obtain interlaminar shear strength. The specimen length was 6 times the thickness, and the span was 4 times the thickness. The tests were performed on a universal testing machine. Three-point bending loading was applied at the loading rate, and the maximum load at which the specimen failed interlaminar shear was recorded.
[0100] Axial tensile properties were tested according to ASTM D3039 standard for tensile testing of composite materials. Both ends of the specimen were sealed and consolidated using polymer composite anchors. The effective gauge length was [length missing]. On a universal testing machine The tensile rate was applied until the specimen fractured, the ultimate tensile load was recorded and the axial tensile strength was calculated. Five valid specimens were measured in parallel for each test group.
[0101] Experimental data:
[0102] Table 2. Test data of mechanical properties of composite braided ropes in the examples and comparative examples.
[0103]
[0104] Analysis of comprehensive mechanism and test results
[0105] Based on the experimental data in Tables 1 and 2, a technical analysis of the mechanism of action of this technical solution is conducted:
[0106] First, the synergistic effect of alternating pulsed electric field and eutectic solvent in fluid dynamics was verified. Data from Example 1 and Comparative Example 1 show that under natural capillary immersion conditions without an applied electric field, the porosity of Comparative Example 1 is as high as 9.12%, and the interlaminar shear strength and tensile strength are significantly deteriorated. This indicates that conventional physical immersion cannot overcome the capillary resistance of the three-dimensional dense hybrid structure, resulting in resin-deficient areas in the core of the braided rope. After using an alternating pulsed electric field in Example 1, the porosity was reduced to 0.76%. The underlying mechanism is that free cations in the eutectic solvent generate periodic oscillation migration in the alternating electric field, thereby triggering alternating electroosmotic flow. This fluid shear force forces the resin system to penetrate into the fiber core voids, eliminating residual gas.
[0107] Secondly, setting alternating parameters is essential to avoid electrochemical side reactions. In Comparative Example 2, a constant DC electric field was used, resulting in a surge in porosity to 18.75% and a catastrophic decline in various mechanical properties. This phenomenon confirms that when conductive carbon fiber bundles act as cathodes in a DC electric field, forming an electrolytic electrode system with the anode plate, continuous electrolytic reactions occur with trace amounts of moisture and polar substances within the resin system, generating large amounts of hydrogen and oxygen. Since the bubbles are difficult to expel from the dense three-dimensional woven structure, severe porosity defects result. The embodiment uses an alternating pulse frequency of 5kHz to 20kHz, preventing charge from accumulating at the interface to the potential threshold for redox reactions during rapid polarity reversal, thus blocking the electrolytic gas generation process while simultaneously obtaining fluid dynamics.
[0108] Third, the interfacial enhancement effect of the in-situ hydrogen bond network is significant in macroscopic mechanics. Compared with Comparative Example 3, Example 1 used a conventional reactive diluent without introducing choline chloride. Although the porosity of Comparative Example 3 was controlled at 1.41% and the impregnation quality was acceptable, its interlayer shear strength was only [missing value]. Far lower than that of Example 1 The essential reason is that after the eutectic solvent is thermally activated and dissociates to release imidazole for bulk cross-linking and curing, the free choline chloride molecules are enriched on the surface of the polar inorganic fiber. The terminal hydroxyl groups of the choline chloride and the silanol groups on the surface of the silicon carbide fiber spontaneously form a dense secondary bonding network, which strengthens the physicochemical anchoring effect between the resin matrix and the inert silicon carbide fiber and improves the efficiency of interfacial shear stress transmission.
[0109] Fourth, the three-dimensional hybrid structure of carbon fiber and silicon carbide fiber provides the necessary interfacial stiffness transition. Comparative Example 4 uses pure carbon fiber weaving, and because silicon carbide fiber is eliminated, its axial tensile strength is affected by the increase in carbon fiber volume fraction. However, its interlaminar shear strength dropped to The introduction of silicon carbide fiber in the hybrid structure plays a role in the transition of interfacial stiffness and interlayer reinforcement, which alleviates the stress concentration phenomenon when pure carbon fiber is subjected to interlayer shear stress and ensures the shear stability of the overall composite rope structure.
Claims
1. A carbon fiber reinforced thermosetting resin-based composite braided rope, characterized in that, The composite braided rope is made by impregnating and distributing a latent impregnation resin system inside and on the surface of a fiber-reinforced substrate; The fiber-reinforced substrate comprises carbon fiber bundles and silicon carbide fiber bundles, wherein the total fiber volume content of the composite braided rope is 55% to 65%, and in the total fiber volume, the carbon fiber bundles account for 70% to 80%, and the silicon carbide fiber bundles account for 20% to 30%. The latent impregnation resin system comprises bisphenol A type epoxy resin and a eutectic solvent, wherein, by weight, every 100 parts by weight of the bisphenol A type epoxy resin contains The eutectic solvent in parts by weight; The eutectic solvent is formed by hydrogen bonding of choline chloride and imidazole, wherein the molar ratio of choline chloride to imidazole is [insert molar ratio here]. ; Before being mixed and woven, the carbon fiber bundles and / or the silicon carbide fiber bundles are surface-cleaned and activated by the eutectic solvent to remove the sizing agent on the fiber surface and introduce hydroxyl active sites on the fiber surface.
2. The carbon fiber reinforced thermosetting resin-based composite braided rope according to claim 1, characterized in that, The carbon fiber bundle is a polyacrylonitrile-based continuous carbon fiber bundle with a surface carbon content greater than or equal to 94%. The silicon carbide fiber bundle is a continuous silicon carbide fiber bundle, and the oxygen mass fraction on the fiber surface is less than or equal to 1.5%. The bisphenol A type epoxy resin in The epoxy equivalent under the given conditions is And in The dynamic viscosity under the given conditions is .
3. The carbon fiber reinforced thermosetting resin-based composite braided rope according to claim 1, characterized in that, The total fiber volume content of the composite braided rope is 60%, the carbon fiber bundle accounts for 75% of the total fiber volume, and the silicon carbide fiber bundle accounts for 25% of the total fiber volume. Each 100 parts by weight of the bisphenol A type epoxy resin contains 20 parts by weight of the eutectic solvent, and the molar ratio of choline chloride to imidazole in the eutectic solvent is [missing information]. .
4. The carbon fiber reinforced thermosetting resin-based composite braided rope according to claim 1, characterized in that, The fiber-reinforced substrate adopts a three-dimensional multi-directional braided structure, with the carbon fiber bundle serving as the axial load-bearing core yarn and the silicon carbide fiber bundle serving as the wear-resistant and interface transition braided yarn interwoven around the core yarn. The ends of the composite braided rope have a portion of the internal continuous carbon fiber bundles led out to serve as conductive connection terminals for an external power source.
5. The carbon fiber reinforced thermosetting resin-based composite braided rope according to claim 1, characterized in that, After the latent impregnation resin system is fully cured, the terminal hydroxyl groups in the choline chloride form a hydrogen bond network with the silanol groups on the surface of the silicon carbide fiber bundle.
6. A method for preparing a carbon fiber reinforced thermosetting resin-based composite braided rope according to any one of claims 1-5 and for reinforcing its components, characterized in that, Includes the following steps: (1) Preparation steps of eutectic solvent: choline chloride and imidazole are heated and mixed to obtain a homogeneous eutectic solvent; (2) Fiber surface pretreatment step: Immerse the carbon fiber bundle and / or silicon carbide fiber bundle in the eutectic solvent, and perform [treatment] under inert gas protection. Constant temperature treatment After minutes, the fiber bundles were removed, rinsed with anhydrous ethanol and dried to obtain surface-modified fiber bundles. (3) Mixed braiding molding step: The surface-modified carbon fiber bundles and silicon carbide fiber bundles are mixed in three dimensions and multi-directionally to obtain a dry mixed braided rope; (4) Latent resin preparation steps: The eutectic solvent and bisphenol A type epoxy resin are mixed and degassed at room temperature to obtain a latent impregnation resin system; (5) Electric field driven impregnation step: The dry-state hybrid rope is immersed in the latent impregnation resin system. An external alternating pulse electric field is applied to induce electroosmotic flow in the resin system within the hybrid rope. After impregnation, the rope is withdrawn, and the resin mass fraction is controlled to be [value missing]. The carbon fiber reinforced thermosetting resin-based composite braided rope is obtained. (6) Component surface anchoring step: The impregnated hybrid rope is wrapped around and pre-tightened to fix it to the surface of the component to be reinforced; (7) Thermal activation in-situ curing step: Apply external heating to the reinforced area to increase the temperature in stages, dissociate the hydrogen bonds in the eutectic solvent to release imidazole, and crosslink and cure the bisphenol A type epoxy resin in situ.
7. The preparation method of carbon fiber reinforced thermosetting resin-based composite braided rope and its component reinforcement method according to claim 6, characterized in that, In step (1), the specific preparation method of the eutectic solvent is as follows: Under inert gas protection, choline chloride and imidazole powder were weighed according to a predetermined molar ratio and placed in a reaction vessel equipped with a reflux condenser. Control the heating temperature to Turn on the mechanical stirrer and stir at a constant temperature. Hours, until the solid mixture transforms into a homogeneous, transparent liquid, cooled to... spare.
8. The preparation method of carbon fiber reinforced thermosetting resin-based composite braided rope and its component reinforcement method according to claim 6, characterized in that, In step (5), the specific process parameters for electric field-driven impregnation are as follows: Connect the parallel anode plate in the impregnation tank to the high potential output terminal of the pulse power supply, and connect the continuous carbon fiber bundle lead-out end of the dry hybrid rope to the low potential output terminal of the pulse power supply. An alternating pulsed electric field is applied, with the electric field strength set as follows: The pulse frequency is Duty cycle is Maintaining the effect of pulsed electric field minute.
9. The preparation method of carbon fiber reinforced thermosetting resin-based composite braided rope and its component reinforcement method according to claim 6, characterized in that, In step (5), during the application of the alternating pulsed electric field, the temperature of the resin system is controlled by a closed-loop temperature control system and an external circulating water cooling jacket. Between, and the highest local temperature does not exceed .
10. The preparation method of the carbon fiber reinforced thermosetting resin-based composite braided rope and the method for reinforcing its components according to claim 6, characterized in that, In step (7), the stepped temperature rise parameters for thermally activated in-situ curing are: Firstly The heating rate was increased to and maintain a constant temperature Pre-curing is carried out within hours; Subsequently The heating rate was increased to and maintain a constant temperature After curing for 2 hours, allow to cool naturally after curing.